A Needs Assessment and Educational Intervention Addressing the Care of Sexual Assault Patients in the Emergency Department. Issue 2 (April 2020) - Chandramani, Ayushi; Dussault, Nicole; Parameswaran, Ramya; Rodriguez, Jaclyn; Novack, Jared; Ahn, James; Oyola, Sonia; Carter, Keme
Abstract : ABSTRACT: Emergency department (ED) providers serve as the primary point-of-contact for many survivors of sexual assault but are often ill-prepared to address their unique treatment needs. Sexual assault nurse examiners (SANEs) are therefore an important resource for training other ED providers. The objective of this project was to create a SANE-led educational intervention addressing this training gap. We achieved this objective by (a) conducting a needs assessment of ED providers' self-reported knowledge of, and comfort with, sexual assault patient care at an urban academic adult ED and, (b) using these results to create and implement a SANE-led educational intervention to improve emergency medicine residents' ability to provide sexual assault patient care. From the needs assessment survey, ED providers reported confidence in medical management but not in providing trauma-informed care, conducting forensic examinations, or understanding hospital policies or state laws. Less than half of the respondents felt confident in their ability to avoid retraumatizing sexual assault patients, and only 29% felt comfortable conducting a forensic examination. On the basis of these results, a SANE-led educational intervention was developed for emergency medicine residents, consisting of a didactic lecture, two standardized patient cases, and a forensic pelvic examination simulation. Preintervention and postintervention surveys showed an increase in respondents' self-perceived ability to avoid retraumatizing patients, comfort with conducting forensic examinations, and understanding of laws and policies. These results show the value of an interprofessional collaboration between physicians and SANEs to train ED providers on sexual assault patient care. Abstract : Supplemental digital content is available in the text.